Assessment of Groundwater Recharge in Semi-Arid Region of Northern Nigeria - Ndubuisi, Obiejesi Luke (Biological Sciences - PJSIR, 2008)
. The average annual groundwater recharge value of three sites, representing the major geological basins of Northern Nigeria, ranged from 169 mm for Maiduguri to 837 mm in Kano area and the recharge coefficient for the zone ranged from 0.26 to 0.56. The month of August accounted for about 53% of the average annual estimate. About 69 mm (70%) of average annual potential natural groundwater recharge was lost, as a result